Android System Call Analysis for Malicious Application Detection - Malik, Sapna (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, Android Malware is coded so wisely that it has become very difficult to detect them. The static analysis of malicious code is not enough for detection of malware as this malware hides its method call in encrypted form or it can install the method at runtime. The System Calls tracing is an effective dynamic analysis technique for detecting malware as it can analyze the malware at the run time. Moreover, this technique does not require the application code for malware detection. Thus, this can detect that Android malware also which are difficult to detect with static analysis of code. The paper presented the framework of detecting malicious application from 81 malware families by analysis of dynamic feature System Calls Invoked with machine learning algorithms.